2010
DOI: 10.1074/jbc.m109.060632
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Mechanism of Insulin Resistance Using a Novel Heterodimerization Strategy to Activate Akt

Abstract: Insulin resistance can occur in response to many different external insults, including chronic exposure to insulin itself as well as other agonists such as dexamethasone. It is generally thought that such defects arise due to a defect(s) at an early stage in the insulin signaling cascade. One model suggests that this involves activation of the mammalian target of rapamycin/S6 kinase pathway, which inactivates insulin receptor substrate via Ser/Thr phosphorylation. However, we have recently shown that insulin r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…At the cellular level, development of insulin resistance is associated with an impairment in the insulin signaling pathway. More specifically, impaired GLUT4 translocation into the cell membrane has been attributed to defects in signaling involving the insulin receptor substrate 1 (IRS-1) (Hotamisligil et al, 1996;Morino et al, 2008), Akt (also known as protein kinase B (PKB)) (Teruel et al, 2001;Tonks et al, 2013) and effectors downstream of Akt (Ng et al, 2010). Adipose tissue also influences glucose homeostasis indirectly by regulating lipid homeostasis (Walther and Farese, 2012) and several factors related to lipid homeostasis have been proposed to contribute also to insulin resistance.…”
Section: Insulin Resistance and Adipose Tissuementioning
confidence: 98%
“…At the cellular level, development of insulin resistance is associated with an impairment in the insulin signaling pathway. More specifically, impaired GLUT4 translocation into the cell membrane has been attributed to defects in signaling involving the insulin receptor substrate 1 (IRS-1) (Hotamisligil et al, 1996;Morino et al, 2008), Akt (also known as protein kinase B (PKB)) (Teruel et al, 2001;Tonks et al, 2013) and effectors downstream of Akt (Ng et al, 2010). Adipose tissue also influences glucose homeostasis indirectly by regulating lipid homeostasis (Walther and Farese, 2012) and several factors related to lipid homeostasis have been proposed to contribute also to insulin resistance.…”
Section: Insulin Resistance and Adipose Tissuementioning
confidence: 98%
“…To investigate the potential selectivity of insulin resistance in adipocytes, we first examined a range of insulin-regulated processes in 3T3-L1 adipocytes rendered insulin-resistant via either exposure to high levels of insulin (CI), glucocorticoids (DEX), or inflammatory cytokines (TNF␣) (24,31). In all three of these model systems, insulin-stimulated glucose transport was significantly blunted (Fig.…”
Section: Insulin Resistance Is Confined To Glucose Metabolism Inmentioning
confidence: 99%
“…Knockdown and knockout studies have shown that Akt, particularly the Akt2 isoform, is required for insulin-stimulated GLUT4 translocation (Cho et al, 2001a,b;Jiang et al, 2003;Katome et al, 2003;McCurdy and Cartee, 2005). Studies in which constitutively active Akt2 has been overexpressed, or in which chemical-genetic approaches have been used to activate Akt2 acutely, suggest that Akt2 alone is fully sufficient to stimulate GLUT4 translocation (Kohn et al, 1996;Ng et al, 2010bNg et al, , 2008. However, comparison of GLUT4 translocation after acute Akt2 activation has been made only upon submaximal insulin stimulation, and it remains unclear how the data fit with the less-well-studied non-PI3K and nonAkt signals that are required for insulin-stimulated GLUT4 translocation Chang et al, 2007;Chiang et al, 2001;Farese et al, 2007;Klip et al, 2014;Sajan et al, 2014b;Sylow et al, 2014;Ueda et al, 2010;Cheney et al, 2011;Govers et al, 2004;Martinez et al, 2010).…”
Section: Introductionmentioning
confidence: 99%